Integrating crops and livestock in subtropical agricultural systems - Wright, Iain A.; Tarawali, Shirley A.; Blümmel, Michael; Gerard, Bruno G.; Teufel, Nils; Herrero, Mario (Wiley, 2012)
As the demand for livestock products increases, and is expected to continue to increase over the next few decades, especially in developing countries, smallholder mixed systems are becoming more intensive. However, with limited land and water resources and concern about the environmental impact of agricultural practices and climate change, the challenge is to find ways of increasing productivity that do not compromise household food security, but rather increase incomes equitably and sustain or enhance the natural resource base. In developed countries there has been increased specialisation of crop and livestock production. In contrast, the majority of livestock in developing countries is kept in mixed crop/livestock systems. Crops (cereal grains and pulses) and crop residues provide the basis of the diet for animals, e.g. cereal straw fed to dairy cattle or sweet potato vines fed to pigs. Animal manure can provide significant nutrient inputs to crops. Water productivity is higher in mixed crop/livestock systems compared with growing crops alone. Mixed systems allow for a more flexible and profitable use of family labour where employment opportunities are limited. They also spread risks across several enterprises, a consideration in smallholder systems that may become even more important under certain climate change scenarios. Integrated crop/livestock systems can play a significant role in improving global food security but will require appropriate technological developments, institutional arrangements and supportive policy environments if they are to fulfil that potential in the coming decades.